15 Years of Microstate Research in Schizophrenia – Where Are We? A Meta-Analysis - Rieger, Kathryn; Diaz Hernandez, Laura; Baenninger, Anja; Koenig, Thomas (Frontiers in Psychiatry, 2016)
Schizophrenia patients show abnormalities in a broad range of task demands. Therefore, an explanation common to all these abnormalities has to be sought independently of any particular task, ideally in the brain dynamics before a task takes place or during resting state. For the neurobiological investigation of such baseline states, EEG microstate analysis is particularly well suited, because it identifies sub-second global states of stable connectivity patterns directly related to the recruitment of different types of information processing modes (e.g. integration of top-down and bottom-up information). Meanwhile, there is an accumulation of evidence that particular microstate-networks are selectively affected in schizophrenia. To obtain an overall estimate of the effect-size of these microstate abnormalities, we present a systematic meta-analysis over all studies available to date relating EEG microstates to schizophrenia. Results showed medium size effects for two classes of microstates, namely a class labelled C that was found to be more frequent in schizophrenia, and a class labelled D that was found to be shortened. These abnormalities may correspond to core symptoms of schizophrenia, e.g. insufficient reality testing and self-monitoring as during auditory verbal hallucinations. As interventional studies have shown that these microstate features may be systematically affected using antipsychotic drugs or neurofeedback interventions, these findings may help introducing novel diagnostic and treatment options.